2020
DOI: 10.1111/bjd.19325
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy and tolerability of biologic therapies in psoriasis: an updated network meta‐analysis

Abstract: Background The rapid expansion of psoriasis biologics has led to an urgent need to understand their relative efficacy and tolerability to inform treatment decisions better and, specifically, to inform guideline development. Objectives To update a 2017 meta-analysis on the comparative efficacy and tolerability of biologic treatments for psoriasis. Methods We searched the MEDLINE, PubMed, Embase and Cochrane databases for randomized controlled trials (RCTs), published up to 7 September 2018, of 11 licensed, NICE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(130 citation statements)
references
References 32 publications
(152 reference statements)
8
117
0
5
Order By: Relevance
“…For example, Sbidian et al [ 15 ] suggested that anti-IL-17 agents (ixekizumab, secukinumab, bimekizumab, and brodalumab), anti-IL-23 agents (risankizumab and guselkumab), and infliximab were significantly more effective, in terms of PASI 90 response rates, than ustekinumab and other anti-TNF agents (adalimumab, certolizumab, and etanercept). Mahil et al [ 13 ] showed that in terms of achieving clear/nearly clear skin status, ixekizumab was associated with the highest SUCRA value followed by risankizumab. Sawyer et al [ 12 ] reported that the anti-IL-17 agents guselkumab and risankizumab were more efficacious than tildrakizumab, ustekinumab, anti-TNF agents, and non-biologic systemic treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sbidian et al [ 15 ] suggested that anti-IL-17 agents (ixekizumab, secukinumab, bimekizumab, and brodalumab), anti-IL-23 agents (risankizumab and guselkumab), and infliximab were significantly more effective, in terms of PASI 90 response rates, than ustekinumab and other anti-TNF agents (adalimumab, certolizumab, and etanercept). Mahil et al [ 13 ] showed that in terms of achieving clear/nearly clear skin status, ixekizumab was associated with the highest SUCRA value followed by risankizumab. Sawyer et al [ 12 ] reported that the anti-IL-17 agents guselkumab and risankizumab were more efficacious than tildrakizumab, ustekinumab, anti-TNF agents, and non-biologic systemic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…While several recent network meta-analyses (NMAs) have been conducted to compare the relative efficacy of treatments for moderate-tosevere plaque psoriasis, knowledge gaps still exist [12][13][14][15][16][17][18][19]. First, PASI 100 results were not available in some of the recent NMAs [13,15]. Second, such NMAs may lack sufficient statistical power to detect potential differences between treatments with the highest PASI 90 and 100 response rates.…”
Section: Introductionmentioning
confidence: 99%
“…Agents targeting the IL-23/Th17 pathway have led to high hurdle responses in psoriasis, in excess of those seen with TNF inhibitors, 3 4 confirming the key pathogenetic role of IL-23/Th17 in the skin in psoriasis. By contrast, in PsA, there are limited head-to-head studies 5 6 and effects of treatment on joints appear more heterogeneous than in the skin.…”
Section: Introductionmentioning
confidence: 87%
“…showing a neutral effect on the principal metabolic parameters. 8 The objective of the study was to compare the safety of methotrexate vs secukinumab in psoriasis patients with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the safety profile in psoriasis patients with concomitant metabolic syndrome treated with methotrexate are scarce 7 . Secukinumab is a fully human monoclonal antibody that selectively blocks IL‐17A showing a neutral effect on the principal metabolic parameters 8 …”
Section: Introductionmentioning
confidence: 99%